Binding Features and Functions of ATG3 - Fang, Dongmei; Xie, Huazhong; Hu, Tao; Shan, Hao; Li, Min (Frontiers in Cell and Developmental Biology, 2021)
Autophagy is an evolutionarily conserved catabolic process that is essential for maintaining cellular, tissue, and organismal homeostasis. Autophagy-related (ATG) genes are indispensable for autophagosome formation. ATG3 is one of the key genes involved in autophagy, and its homologs are common in eukaryotes. During autophagy, ATG3 acts as an E2 ubiquitin-like conjugating enzyme in the ATG8 conjugation system, contributing to phagophore elongation. ATG3 has also been found to participate in many physiological and pathological processes in an autophagy-dependent manner, such as tumor occurrence and progression, ischemia–reperfusion injury, clearance of pathogens, and maintenance of organelle homeostasis. Intriguingly, few studies have recently discovered the autophagy-independent functions of ATG3, including cell differentiation and mitosis. Here, we summarize the current knowledge of ATG3 in autophagosome formation, highlight its binding partners and binding sites, review its autophagy-dependent functions, and provide a brief introduction into its autophagy-independent functions.